Ancient Africa: a historical/historiographic approach to the “The tale of the Shipwrecked Sailor” - Bakos, Margaret M. (Romanitas - Revista de Estudos Grecolatinos, 2017)
This paper aims to analyse the role played by the scribe in the ancient Egyptian society, as well as the characteristics and forms of organization of human relations in the African context at the time, as configured in the “The tale of the Shipwrecked Sailor”. These issues are still poorly explored in the historiography in Portuguese. Therefore, this paper comments four texts, written in Portuguese, on the subject.